Fish Nutritional Value as an Approach to Children's Nutrition - Maulu, Sahya; Nawanzi, Kundananji; Abdel-Tawwab, Mohsen; Khalil, Hala Saber (Frontiers in Nutrition, 2021)
Fish is a relatively cheap and accessible source of animal protein for human consumption even in rural communities. It is critical for global food and nutrition security, and its consumption continues to increase. As a highly nutritious food, fish consumption is highly recommended for children and expectant mothers for normal growth and development. The present paper explores the nutritional value of fish as approach to nutrition in children and its benefits. The findings reveal that fish is a valuable source of essential amino acids (EAA) and polyunsaturated fatty acids (PUFAs) that play important physiological functions for maintenance and development of fetuses, neonates, and infant brains. Therefore, it could be a valuable tool in the fight against food insecurity and malnutrition. However, fish and fish products are also highly susceptible to contamination by various organic and inorganic compounds that threaten public health. Particularly, heavy metals and biogenic amines (BAs) have shown adverse effects when contaminated fish is consumed, and the effects in children have been worse. Hence, while fish consumption is highly recommended for children's nutrition, the safety and quality of the product should always be checked to safeguard public health.